2015
DOI: 10.1002/mc.22439
|View full text |Cite
|
Sign up to set email alerts
|

Homeobox A9 directly targeted by miR‐196b regulates aggressiveness through nuclear Factor‐kappa B activity in non‐small cell lung cancer cells

Abstract: MicroRNAs (miRNAs) are recognized as crucial posttranscriptional regulators of gene expression, and play critical roles as oncogenes or tumor suppressors in various cancers. Here, we show that miR-196b is upregulated in mesenchymal-like-state non-small cell lung cancer (NSCLC) cells and lung cancer tissues. Moreover, miR-196b upregulation stimulates cell invasion and a change in cell morphology to a spindle shape via loss of cell-to-cell contacts. We identified homeobox A9 (HOXA9) as a target gene of miR-196b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 51 publications
3
46
0
Order By: Relevance
“…Studies have shown that HoxA9 accelerated restoration of endothelial damage [16]. Except for the protective effects of HoxA9 on the endothelium, Hox A9 has also been reported to promote E-cadherin expression [17]. Furthermore, HOXA9 potently attenuated the expression of matrix metallopeptidase 9 (MMP 9) by controlling the binding of nuclear factor-kappa B to the promoter of MMP 9 genes, respectively [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that HoxA9 accelerated restoration of endothelial damage [16]. Except for the protective effects of HoxA9 on the endothelium, Hox A9 has also been reported to promote E-cadherin expression [17]. Furthermore, HOXA9 potently attenuated the expression of matrix metallopeptidase 9 (MMP 9) by controlling the binding of nuclear factor-kappa B to the promoter of MMP 9 genes, respectively [17].…”
Section: Discussionmentioning
confidence: 99%
“…Except for the protective effects of HoxA9 on the endothelium, Hox A9 has also been reported to promote E-cadherin expression [17]. Furthermore, HOXA9 potently attenuated the expression of matrix metallopeptidase 9 (MMP 9) by controlling the binding of nuclear factor-kappa B to the promoter of MMP 9 genes, respectively [17]. It has been suggested that HoxA9 within the lung may therefore play a critical role in contributing to the regulation of alveolar-capillary permeability and promoting lung repair.…”
Section: Discussionmentioning
confidence: 99%
“…Lung cancer is one of the most common malignancies and remains the leading cause of cancer-related deaths worldwide [1]. In the various histological subtypes, non-small cell lung cancer (NSCLC) is the most prevalent subtype, which accounts for approximately 80% in all cases of diagnosed with lung cancer [1, 2].…”
Section: Introductionmentioning
confidence: 99%
“…In the various histological subtypes, non-small cell lung cancer (NSCLC) is the most prevalent subtype, which accounts for approximately 80% in all cases of diagnosed with lung cancer [1, 2]. NSCLC is characterized by a high mortality, and the overall five-year survival rate remains less than 15% [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation